Photocatalytic degradation of methyl orange mediated by a silica coated nanomagnet porphyrin hybrid - Castro, Kelly A. D. F. (2022)
The photocatalytic activity of a silica coated nanomagnet porphyrin hybrid (NPH) and of the corresponding porphyrin precursors (H2P and ZnP) was evaluated in the degradation of the methyl orange dye (MO) under visible light irradiation. The catalytic degradation of MO was performed under air, in the absence and in the presence of aqueous hydrogen peroxide. The results show that the hybrid NPH was the most effective photocatalyst causing the total degradation of MO after 270 min of white light irradiation (150 mW cm−2 ) in the presence of hydrogen peroxide. The remarkable photocatalytic activity of this NPH, associated with the possibility of its reuse, makes this material a promising photocatalyst.